Interpretation of Tauḥīd Verses from Said Nursi's Perspective: An Esoteric Approach and Its Influence on Islamic Thought - Asif Trisnani; Muhammad Thoriqul Islam; Raisya Miftakhul Rahma; Nawa Marjany (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2024)
In the modern context, it is important for Muslims to have a concept of monotheism that does not just remain academic but also helps in strengthening one's faith. Nursi introduces two dimensions of monotheism: birth monotheism and true monotheism, both of which aim to nurture faith in everyday life. Understanding both the exoteric and esoteric interpretations of monotheistic verses is crucial. This research delves into Nursi's esoteric approach to Tauḥīd ‘monotheistic’ verses and their impact on Islamic thought. The qualitative research design involves a literature review, gathering data from journals, proceedings, books, and documentaries. The data is analyzed using content analysis techniques, as well as esoteric and historical approaches. The research findings reveal that Nursi's esoteric interpretation of monotheistic verses is in line with other Sufi mufassirs, with two significant differences. Firstly, Nursi's esoteric approach, particularly in tafakkur, offers tangible examples that can be experienced physically. Secondly, as a member of the Naqshbandi Tariqa, Nursi consistently refers to asmā' al-ḥusnā and associates it with manifestations reflected in all entities when interpreting the Qur'an. Nursi's interpretation of monotheistic verses has a strong influence at the international level and a socio-religious impact at the national level. However, his interpretation remains significant in addressing religious matters in Indonesia.